1993
DOI: 10.1128/jb.175.3.589-596.1993
|View full text |Cite
|
Sign up to set email alerts
|

Construction and biochemical characterization of recombinant cytoplasmic forms of the IucD protein (lysine:N6-hydroxylase) encoded by the pColV-K30 aerobactin gene cluster

Abstract: The aerobactin gene cluster in pColV-K30 consists of five genes (iucABCD iutA); four of these (iucABCD) are involved in aerobactin biosynthesis, whereas the fifth one (iutA) encodes the ferriaerobactin outer membrane receptor. iucD encodes lysine:NM-hydroxylase, which catalyzes the first step in aerobactin biosynthesis. Regardless of the method used for cell rupture, we have consistently found that IucD remains membrane bound, and repeated efforts to achieve a purified and active soluble form of the enzyme hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…IucD was able to utilize NADH as a cofactor, although the activity of the enzyme was twofold lower than the corresponding activity with NADPH as a cofactor (22). PvdA, on the other hand, was not able to use NADH in place of NADPH as a cofactor.…”
Section: Discussionmentioning
confidence: 97%
“…IucD was able to utilize NADH as a cofactor, although the activity of the enzyme was twofold lower than the corresponding activity with NADPH as a cofactor (22). PvdA, on the other hand, was not able to use NADH in place of NADPH as a cofactor.…”
Section: Discussionmentioning
confidence: 97%
“…A key step in these pathways involves the N 5 -hydroxylation of L-ornithine in the case of pyoverdin (17,34) and the N 6 -hydroxylation of L-lysine in the case of aerobactin (22,29,30). These hydroxylations are catalyzed by flavin monooxygenases.…”
Section: Discussionmentioning
confidence: 99%
“…The mbtG gene product from the mbt cluster has been anticipated to be a lysine N6-hydroxylase (9,15). Previous studies with N6-hydroxylase from aerobactin biosynthetic cluster had suggested that these proteins belong to the family of flavoprotein monooxygenases and consume molecular oxygen during catalysis (31,32). The enzymatic reactions with MbtG protein were carried out with N6-lauroyl Z-Lys-OMe (II) in the presence of NADPH and FAD, in air saturated buffers (Fig.…”
Section: Mbtg Produces Hydroxamate Groups In Mycobactin Necessary Formentioning
confidence: 99%